The upper pole of the thyroid gland: surgical managment - Suiffet, Walter (Cirugía del Uruguay, 1973)
The author comments on anatomical characteristics of superior pole of thyroid gland and its incidence on surgical technique during the course of thyroidectomies. Surgical steps in the management of the superior pole of thyroid are analyzed. They are: exposure, disinhibition, hemostasis of superior pedicle and descent of pole. Adequate manouvres for each step are considered, with stress on anatomical knowledge and its application during surgery. Risk involved in such manouvres is mentioned; and exhaustively analyzed; possibility of haemorrhage, nerve aggression, visceral lesions and aggression of parathyroid glands.